EFFECT OF LEVERAGE, COMPANY SIZE AND WORKING CAPITAL TURNOVER ON FIRM VALUE WITH PROFITABILITY AS MEDIATION VARIABLE - Menik Indrati; Listya Ayu Artikasari (Jurnal Ekonomi, 2023)
The purpose of this study was to analyze the effect of leverage, firm size and working capital turnover on firm value with profitability as a mediating variable. This research consists of four independent variables consisting of Leverage proxied by DER, Company Size proxied by Ln(Asset), Working Capital Turnover which is proxied by WCTO and Profitability which is proxied by ROE, as well as one dependent variable namely Company Value proxied by PBV . In this study there were 153 companies that met the criteria from a total of 719 observations with research objects in non-financial sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. The measurement of this study used Econometric Views 12 (Eviews 12 ). The results of this study indicate that leverage has a negative effect on profitability. Firm size has a positive effect on profitability. Working Capital Turnover has no effect on Profitability. Leverage has no effect on Firm Value. Firm size has a positive effect on firm value. Working Capital Turnover has no effect on Company Value. And Profitability can mediate Firm Size to Firm Value. This research can also be taken into consideration for investors and shareholders to be more careful in receiving financial statement information provided by companies in making investment decisions because this research focuses more on internal financial reports.